Produksi Asap Cair Kayu Kesambi (Schleichera oleosa Merr) dan Aplikasinya Sebagai Flavouring Daging Sei - Marthen Y. Saubaki (Partner, 2013)
Production of Liquid Smoke Wood kesambi (Schleicera oleosa Merr) and Its Application For Flavouring Meat Sei. The use of liquid smoke in the manufacture of wood kesambi need to be studied to obtain a certain concentration of liquid smoke to give a flavour of traditional sei meat. This study aims to: 1) determine the components of liquid smoke kesambi flavour giver on sei meat processing. 2) determine the effect of the application of liquid smoke kesambi the chemical, physical, and microbiological sei meat processing. Production of liquid smoke made of wood kesambi pyrolysis temperature of 400OC, then do redistilation at ± 100°C. The second stage is the creation sei meat using liquid smoke to concentrations of 10%, 20% and 30%. Application of liquid smoke kesambi showed different results, both in terms of chemical components, physical and sensory properties of the resulting sei. Sei meat roasting results in a decrease of phenol, carbon, total acid, pH, and levels of tar, after roasting physically increase the level of hardness. Liquid smoke kesambi with concentration variation combined storage at 4°C to inhibit bacterial growth for 7 days of storage. Key words: Meat Sei, Liquid Smoke, flavour, Kesambi.